Integrating Sunda clouded leopard (Neofelis diardi) conservation into development and restoration planning in Sabah (Borneo). (July 2019) - Kaszta, Żaneta; Cushman, Samuel A.; Hearn, Andrew J.; Burnham, Dawn; Macdonald, Ewan A.; Goossens, Benoit; Nathan, Senthilvel K.S.S.; Macdonald, David W.
Abstract: Changes in land use/cover are the main drivers of global biodiversity loss, and thus tools to evaluate effects of landscape change on biodiversity are crucial. In this study we integrated several methods from landscape ecology and landscape genetics into a GIS-based analytical framework, and evaluated the impacts of development and forest restoration scenarios on landscape connectivity, population dynamics and genetic diversity of Sunda clouded leopard in the Malaysian state of Sabah. We also investigated the separate and interactive effects of changing mortality risk and connectivity. Our study suggested that the current clouded leopard population size is larger (+26%) than the current carrying capacity of the landscape due to time lag effects and extinction debt. Additionally, we predicted that proposed developments in Sabah may decrease landscape connectivity by 23% and, when including the increased mortality risk associated with these developments, result in a 40–63% decrease in population size and substantial reduction in genetic diversity. These negative impacts could be mitigated only to a very limited degree through extensive and targeted forest restoration. Our results suggest that realignment of roads and railways based on resistance to movement, without including mortality risk, might be misleading and may in some cases lead to decrease in population size. We therefore recommend that efforts to optimally plan road and railway locations base the optimization on effects of development on population size, density and distribution rather than solely on population connectivity. Highlights: Current clouded leopard population size 26% larger than habitat carrying capacity. Developments decrease landscape connectivity by 23%. 40–63% decrease in clouded leopard population size with developments. Mitigation to limited degree through extensive and targeted forest restoration.